The burden of caregivers to patients with schizophrenia: a bibliographic literature review - Hansen, Nayara Fernanda (2014)
An integrative literature review was performed with the objective to identify the evidence available in national and international scientific publications on the responsible reasons for the occurrence of burden among caregivers to patients with schizophrenia. Data collection was performed on Pubmed, LILACS and CINAHL databases by crossing the descriptors sobrecarga/burden, família/family and esquizofrenia/schizophrenia. A total of 14 publications meeting the inclusion criteria were found. The results showed that the reasons for the occurrence of burden are associated with the symptoms of schizophrenia, lack of social support, concerns about the future, changes in social life, daily care, initial phase of schizophrenia, changes in the routine, prejudice, sociodemographic factors and socioeconomic factors, as well as financial difficulties. These findings contribute for establishing the foundations for implementing effective interventions aimed at caregivers, with a view to reducing the burden caused by schizophrenia and improving the patient’s prognosis. Descriptors: Caregivers; Schizophrenia; Psychiatric Nursing.